The Historical Epistemology of Pre-Curricular Zoology: From Portuguese America to Empire of Brazil (1550-1837): (Research, Society and Development, 2022)
Scientific researches developed over the centuries acted directly in the educational context of Sciences as school knowledge. Bachelard's concept of historical epistemology argues that science is a collective and non-linear social construction. In turn, the school curriculum has in its scope the systematization of socially valid knowledge chosen by an elite. This essay aims to contextualize Bioscience Zoology in the light of Bachelard and historical epistemology before being systematized in the first curricular policy documented in 1837 by Colégio Imperial de Pedro II. Therefore, the term “pre-curricular zoology” was used as a generic concept to designate the period prior to the year 1837. The influence of three countries in zoological research on national soil is discussed, the Netherlands, Portugal and Austria with their greatest interests being zoological medical research, discover utilities and taxonomic research respectively.